2017
DOI: 10.3389/fncir.2017.00091
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of Prefrontal Cortex in Non-Human Primates by Dopaminergic Receptors during Rule-Guided Flexible Behavior and Cognitive Control

Abstract: The prefrontal cortex (PFC) is indispensable for several higher-order cognitive and executive capacities of primates, including representation of salient stimuli in working memory (WM), maintenance of cognitive task set, inhibition of inappropriate responses and rule-guided flexible behavior. PFC networks are subject to robust neuromodulation from ascending catecholaminergic systems. Disruption of these systems in PFC has been implicated in cognitive deficits associated with several neuropsychiatric disorders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 124 publications
1
13
0
Order By: Relevance
“…Embryos lacking HTT have disrupted PRC2mediated regulation of gene expression (Seong et al, 2010). Similar to our findings in Htt cKOs, PRC2 loss-of-function in SPNs leads to neurodegeneration (Von Schimmelmann et al, 2016). Therefore, Htt loss in SPNs may disrupt PRC2-dependent regulation of SPN-specific genes.…”
Section: (Legend Continued On Next Page)supporting
confidence: 82%
See 1 more Smart Citation
“…Embryos lacking HTT have disrupted PRC2mediated regulation of gene expression (Seong et al, 2010). Similar to our findings in Htt cKOs, PRC2 loss-of-function in SPNs leads to neurodegeneration (Von Schimmelmann et al, 2016). Therefore, Htt loss in SPNs may disrupt PRC2-dependent regulation of SPN-specific genes.…”
Section: (Legend Continued On Next Page)supporting
confidence: 82%
“…Some axonal TdTomato signal was observed in the GPe of D1-Cre mice, because DP-SPNs send axon collaterals through the GPe (Figure 1E, top;Cazorla et al, 2014). A2A-Cre expression was restricted to IP-SPNs; however, D1-Cre-expressing cells were present in the cortices of D1-Cre mice, because subsets of cortical neurons express the dopamine receptor D1 (Vijayraghavan et al, 2017). We found that $15% of layer 2/3, $15% of layer 4, and $40% of layer 5/6 NeuN + neurons express D1-Cre in the M1 motor cortex, which harbors pyramidal neurons that project to dorsal striatum that is affected in HD (Figures S1A-S1C).…”
Section: Conditional Deletion Of Htt In Ip-spns and Dp-spnsmentioning
confidence: 99%
“…Cortical DA transmission sustains neural activity, facilitating the planning of complex behavioral sequences, impulse control, and reward processing [ 11 , 17 ]. Though most attention has been paid to cortical DA 1 receptors, accumulating evidence indicates that DA 2/3 Rs also modulate cortical cell excitability, influencing perseverative behaviors and behavioral inhibition, perhaps through actions on subcortical projection sites [ 11 , 49 ]. The elevated cortical DA 2/3 R availability in our high-risk youth might aggravate susceptibility to these maladaptive behaviors, as greater PFC DA 2/3 R-mediated neurotransmission has been associated with impulsive behaviors in laboratory animals [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The executive attention network is a neural network involving the anterior cingulate cortex and prefrontal cortex while various memory processes also include brain regions such as the prefrontal cortex, hippocampus, and entorhinal cortex. Pharmacological manipulation of dopaminergic tone and receptors impacts cognitive capacities [5]. Genetic variation in dopaminergic genes is associated with cognitive performance in both healthy and clinical populations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%